Answer:
![11, 13, 15](https://img.qammunity.org/2022/formulas/mathematics/college/ojaqr0bfetdn5war8tw6hnsvdgk61tf2vi.png)
B) 6x + 16 = 82
Note: I just kept my wrong approach.
Explanation:
Let first define an odd integer.
Considering
,
is an odd integer.
Now, three consecutive odd integers are
,
and
![a_3 = 2k+5](https://img.qammunity.org/2022/formulas/mathematics/college/vs17nmp321yci7livqwlvqvd3o43s921dy.png)
The sum of the first, two times the second and three times the third can be written as
![a_1 + 2a_2 + 3a_3 = 2k+1 + 2(2k+3)+3(2k+5)](https://img.qammunity.org/2022/formulas/mathematics/college/8lvob7wz0c53riw269y43srghvo5ckc8m4.png)
Expanding and simplifying
![2k+1 + 2(2k+3)+3(2k+5) = 2k+1 +4k+6+6k+15 = 12k+22](https://img.qammunity.org/2022/formulas/mathematics/college/92ijl64vchs7lwf9llmip2y4fgto07gaz4.png)
This is what I have done initially, but considering
to be an odd integer, three consecutive integers can be written as
such that
![x\in\mathbb{Z}: 2k+1](https://img.qammunity.org/2022/formulas/mathematics/college/u5q4s4ph1gitfusk51j7pqyvknypf5fhtv.png)
Therefore,
![x+2(x+2)+3(x+4)=82 \implies x+2x+4+3x+12 = 82 \implies 6x+16 = 82](https://img.qammunity.org/2022/formulas/mathematics/college/79vyljvn8apjp2plc973384qvocyyz11eg.png)
and
![6x+16 = 82 \implies 6x = 66 \implies x = 11](https://img.qammunity.org/2022/formulas/mathematics/college/f9m1owkgapn0hptkerx9srum7holroz9io.png)
The three consecutive odd integers such that the sum of the first, two times the second and three times the third is 82 are
![11, 13, 15](https://img.qammunity.org/2022/formulas/mathematics/college/ojaqr0bfetdn5war8tw6hnsvdgk61tf2vi.png)